Massive Acquisition of Ultraviolet Color Excess Information from GALEX and UVOT Bands - Dongliang Yang; Mingxu Sun; Biwei Jiang; Wenyuan Cui; Ruoyi Zhang; Luyao Shi; Jiachen Wei (The Astrophysical Journal Supplement Series)
This study employs stellar parameters from spectroscopic surveys and Zhang et al. (2023) based on Gaia BP/RP (XP) spectra, along with photometric data from Galaxy Evolution Explorer (GALEX), UV/Optical Telescope (UVOT), and Gaia, to obtain extensive ultraviolet color excess information for the relevant bands of GALEX and UVOT. By considering the impact of stellar parameters ( T _eff , [Fe/H], and ${\rm{log}}\,g$ ) on intrinsic color indices and utilizing the blue-edge method combined with a random forest algorithm, an empirical relationship between stellar parameters and intrinsic ultraviolet color indices is established. By combining observed color indices, the study derives color excesses for 11,624,802 and 65,531 stars in the GALEX/near-UV and far-UV bands and for 336,633; 137,739; and 253,271 stars in the UVOT/ uvw 1, uvm 2, and uvw 2 bands, constructing corresponding ultraviolet extinction maps. Notably, the color excess data for the GALEX/near-UV band show a tenfold increase from previous results, with the extinction map covering approximately two-thirds of the sky at a resolution of 0 $\mathop{.}\limits^{\unicode{x000B0}}$ 4. The typical uncertainties in the ultraviolet color excesses are 0.21 mag, 0.30 mag, 0.19 mag, 0.24 mag, and 0.21 mag for ${E}_{{\rm{NUV}},G_{{\rm{RP}}}}$ , ${E}_{{\rm{FUV}},G_{{\rm{RP}}}}$ , ${E}_{uvw1,G_{{\rm{RP}}}}$ , ${E}_{uvm2,G_{{\rm{RP}}}}$ , and ${E}_{uvw2,G_{{\rm{RP}}}}$ , respectively. By comparing the spatial distributions of R _V derived from ultraviolet and Gaia optical band measurements with those obtained from infrared and optical data in previous works, it is evident that the R _V distributions based on the ultraviolet data show noticeable differences, with some regions even exhibiting opposite trends. This suggests that a single-parameter R _V extinction law may not be sufficient to simultaneously characterize the extinction behavior across infrared, optical, and ultraviolet bands.